Klausula Eksonerasi Dalam Perjanjian Baku Dan Konsumen: Studi Tentang Perlindungan Hukum Dalam Perjanjian Penitipan Barang Di Terminal Tirtonadi Surakarta - Zainudin, Muhamad; , Kelik Wardiono, S.H. , M.H. , cdDR; , Darsono, S.H. , M.H (2016)
This study was based on legal research conducted by the non-doctrinal approach that is qualitative descriptive. The problem is how the binding force of standard clauses in the agreement in Terminal Tirtonadi vehicle care Surakarta and how the legal protection of consumers involved in vehicle care agreement in Terminal Tirtonadi Surakarta. The results showed that in vehicle care agreement made between business and consumers contained a standard clause that the exoneration clause.